O militante em cena: Gianfrancesco Guarnieri e Eles não usam black tie - Silva, Carlos Rogério Gonçalves da [UNESP] (2015)
The play Eles não usam black tie (They don't wear black tie) was finished in 1956. Its first performance occurred two years later in Arena Theatre in São Paulo, causing immediate impact in the public and catching intellectual and academic circles attention. The protagonism of a poor labor family in Rio de Janeiro was a welcome innovation to the Brazilian theatrical scenario, as well as the innovative techniques of performing in arena. In the fifties, the political environment was agitated over the difficult succession of Getulio Vargas and the collective euphoria coming from the national-development plan of Juscelino Kubitschek. The Communist Party of Brazil (PCB) was trying the reorganize itself in the face of internal challenges and crisis coming from outside: the speech delivered by Nikita Kruschev denouncing Stalin's crimes in the Soviet Union. This decade was also important for the introduction of brechtian epic theatre and for an intense debate over the political role of national dramaturgy. To which extent the political militancy and the dramaturgic sensibility of Gianfrancesco Guarnieri were affected by those influences? Can the play Eles não usam black tie be thought as a privileged historical source to dialogue with the political and esthetic conjuncture in which it was conceived? It can be observed a dialectical relation between Guarnieri's political militancy and the guidelines given by PCB at the time, the principles of bourgeois drama and the brechtian epic theatre in a text full of dilemmas and contradictions of Populism.